Health-related quality of life after heart surgery – Identification of high-risk patients: A cohort study. (April 2020) - Schaal, Nora K.; Assmann, Alexander; Rosendahl, Jenny; Mayer-Berger, Wolfgang; Icks, Andrea; Ullrich, Sebastian; Lichtenberg, Artur; Akhyari, Payam; Heil, Martin; Ennker, Jürgen; Albert, Alexander
Abstract: Background: This cohort study evaluated factors, which have been shown to be relevant for Health-Related Quality of Live (HRQL) after cardiac surgery and investigated the combinatory impact on HRQL. Additionally, the aim was to introduce a first attempt to developing a risk estimation model which could identify patients at risk for impaired HRQL. Methods: For this single-centre cohort study, 6099 cardiac surgical patients (60% isolated coronary bypass surgery) filled in the Nottingham Health Profile (NHP) for the evaluation of HRQL six months after surgery and provided information regarding their medical and socio-demographic status. For the NHP scores the deviation to the matched normative data of a healthy sample was calculated. A robust linear regression examined factors that influence HRQL. As a next step, based on the regression model, a risk estimation model was developed which is a first attempt to classify patients into risk categories. Results: Male gender, age below 60 or between 60 and 74 years, living alone, no occupation, bypass surgery, NYHA status II, III or IV and chest pain were identified as risk factors to determine impaired HRQL. The model explains 29.13% of the variance. Based on the risk estimation model 27.4% were classified as medium or high risk. Conclusions: For the first time a multilevel method was applied to evaluate HRQL after heart surgery showing that socio-demographic variables are important co-factors to dyspnea and chest pain. We take a first attempt in developing a new approach that should encourage further research in this field to frame a screening tool that may help identifying patients at risk in the future. Graphical abstract: Image 1 Highlights: Several factors influence health-related quality of life (QoL) after cardiac surgery. Here the combinatory impact of these factors was examined with a multilevel approach. Socio-demographic variables are important co-factors to dyspnea and chest pain. We introduce a new approach that may help identify patients at risk for impaired QoL.